2004
DOI: 10.1017/s0014479703001601
|View full text |Cite
|
Sign up to set email alerts
|

FARMERS' PERCEPTION OF THE STRIGA PROBLEM AND ITS CONTROL IN NORTHERN NIGERIA

Abstract: The parasitic angiosperms, Striga hermonthica and S. gesnerioides, obligate root parasites endemic in sub-Saharan Africa, constitute severe constraints to cereal and legume production in West and Central Africa. Over the years, a range of effective component technologies has been identified for Striga control in Africa. The potential of these technologies has been demonstrated under researcher-managed conditions. To promote farmer testing of the technologies, community workshops were conducted in 42 rural comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 13 publications
7
46
0
3
Order By: Relevance
“…In addition, Johnson et al (1997) showed that the proportion of 0. glaberrima and 0. sativa plants that appear stunted, is related to the number of Striga plants present. The increasing incidences and severity of Striga damage is linked to poor soil fertility which is due to lack of farm yard manure and inorganic fertilizers (Emechebe et al, 2004).…”
Section: Conditions Favoring Striga Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Johnson et al (1997) showed that the proportion of 0. glaberrima and 0. sativa plants that appear stunted, is related to the number of Striga plants present. The increasing incidences and severity of Striga damage is linked to poor soil fertility which is due to lack of farm yard manure and inorganic fertilizers (Emechebe et al, 2004).…”
Section: Conditions Favoring Striga Growthmentioning
confidence: 99%
“…that infect rice:-S. hermonthica, S. asiatica, S. aspera and S. forbesii. In the rural communities of Northern Nigeria, it has been reported that crop yield losses due to S. hermonthica infections were about 70-100% (Emechebe et al, 2004). It has also been reported that crops can show resistance characteristic in one area and succumb in another because resistance can be broken by the existing biotypes (Gethi et al 2005).…”
Section: Conditions Favoring Striga Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…asiatica is widely regarded by scientists as a biological indicator of land degradation and its parasitic activities and impacts on the maize crop are well documented (for example, see Nickrent and Musselman 2000;Emechebe et al, 2004;Parker and Riches, 1993). It grows primarily in soils with low fertility levels, since it is a poor nitrogen metaboliser, yet its presence in the study area is indicative of a deeper land degradation and soil quality problem (Press and Gurney, 2000).…”
Section: B): Understanding the Rural Livelihood Contextmentioning
confidence: 99%
“…One single wellestablished S. asiatica plant can produce more than 100 000 tiny seeds of approximately 0Á4 Â 0Á3 mm in size, each weighing between 15-26 mg (Mohamed et al, 1998). These are usually dispersed by wind and hydrological processes (Nickrent and Musselman, 2004), although the contamination of grain stocks, shared use of contaminated farm implements (Press and Gurney, 2000), and transfer by livestock are also important (Emechebe et al, 2004). The seeds can then remain dormant in the soil for up to 20 years before attacking the crop (Parker and Riches, 1993), though in field conditions, a dormancy period of 10-15 years is more common.…”
Section: Introductionmentioning
confidence: 99%